First revision of the apodid holothurian genus Patinapta Heding, 1928 (Synaptidae) in Japanese waters, with establishment of four new species from Kyushu Island and Ryukyu Islands, southwestern Japan - Yamana, Yusuke; Hirashima, Kentarou; Sato, Masanori; Yamamori, Luna (Zootaxa, 2025)
Four new species of the genus Patinapta Heding, 1928 are erected from the Kyushu Island and Ryukyu Islands in southwestern Japan, based on specimens from the Wakayama Prefectural Museum of Natural History (WMNH). The ossicles as well as the internal and external morphological features of these species showed clear differences, contrary to our original expectations. In particular, the morphology of the calcareous rings, previously considered of little use for diagnosis, is suggested in our study to be a useful feature for future phylogenetic studies. We describe here two species, P. deformis sp. nov. and P. parvaspiculus sp. nov. from Yoron-jima Island, Kagoshima; P. neglectus sp. nov. from Kagoshima Bay, Kagoshima; and one species, P. edentatus sp. nov., from Ishigaki-jima Island, Okinawa. Together with the two previously reported species P. ooplax (von Marenzeller, 1882) and P. taiwaniensis Chao, Rowe & Chang, 1988, there are now six Japanese taxa of Patinapta. In the present study, the six species occurring in Japanese waters are distinguished and presented on the basis of morphology-based sorting keys to enable correct species identification in the future.